Genomic prediction modeling of soybean biomass using UAV‐based remote sensing and longitudinal model parameters. Issue 3 (30th September 2021) - Toda, Yusuke; Kaga, Akito; Kajiya‐Kanegae, Hiromi; Hattori, Tomohiro; Yamaoka, Shuhei; Okamoto, Masanori; Tsujimoto, Hisashi; Iwata, Hiroyoshi
Abstract: The application of remote sensing in plant breeding can provide rich information about the growth processes of plants, which leads to better understanding concerning crop yield. It has been shown that traits measured by remote sensing were also beneficial for genomic prediction (GP) because the inclusion of remote sensing data in multitrait models improved prediction accuracies of target traits. However, the present multitrait GP model cannot incorporate high‐dimensional remote sensing data due to the difficulty in the estimation of a covariance matrix among the traits, which leads to failure in improving its prediction accuracy. In this study, we focused on growth models to express growth patterns using remote sensing data with a few parameters and investigated whether a multitrait GP model using these parameters could derive better prediction accuracy of soybean [ Glycine max (L.) Merr.] biomass. A total of 198 genotypes of soybean germplasm were cultivated in experimental fields, and longitudinal changes of their canopy height and area were measured continuously via remote sensing with an unmanned aerial vehicle. Growth parameters were estimated by applying simple growth models and incorporated into the GP of biomass. By evaluating heritability and correlation, we showed that the estimated growth parameters appropriately represented the observed growth curves. Also, the use of these growth parameters in the multitrait GP model contributed to successful biomass prediction. We conclude that the growth models could describe the genetic variation of soybean growth curves based on several growth parameters. These dimension‐reduction growth models will be indispensable for extracting useful information from remote sensing data and using this data in GP and plant breeding. Core Ideas: Application of growth models and unmanned aerial vehicle (UAV) remote sensing in genomic prediction was investigated. The growth of soybean plants was estimated from canopy area and height using a UAV. Growth models were used to determine growth patterns of the breeding population. The inclusion of growth parameters improved prediction accuracy of biomass.